Analysis of CAMEL ratio on financial distress banking companies in Indonesia - Fachrul Ferdiansyah; Endang Tri Widyarti (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2022)
The purpose of this research is to determine the influence of banking financial ratio on Financial Distress. The independent variables used in this research are CAR, NPL, BOPO, ROA and LDR, also the dependent variable that is used in this research is Financial Distress. The population used in this research are the 48 banking companies that is listed in the Indonesia Stock Exchange during the period of 2016-2020, and the samples used are 40 manufacture companies which were taken by using purposive sampling method. The analysis method used in this research is logistic regression and is processed using SPSS Statistics 25 software. The result of the this research states that ROA has a significant effect on Financial Distress, while CAR, NPL, BOPO and LDR has no significant effect towards Financial Distress.